Pengaruh Trust, Resiko, Manfaat dan Kemudahan terhadap Minat Menggunakan Fintech dengan Kecerdasan Emosi sebagai Variabel Intervening - Mohtar Khudori; Citra Ayudiati (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
Digital information and communication are very necessary for human life. The aim of this research is to analyze the influence of trust, risk, benefits, and convenience on interest in using fintech with emotional intelligence as an intervening variabel. The method used in this research is the SAMPLS reflective measurement test. The sample used was 43 Cokroaminoto University student respondents who used or had used fintech using random sampling. Based on the analysis results obtained by Trust, risks, benefits, and convenience have a significant influence on interest in using fintech. Trust, risk, benefits, and convenience have a significant effect on emotional intelligence. Trust, risk, benefits, and convenience have a significant influence on interest in using fintech with emotional intelligence as an intervening variabel